Publishing Outcomes of Abstracts Presented at the European Society of Pediatric Otorhinolaryngology Congress in 2018: A Web-Based Analysis - Gökler, Ozan; Coşkuntürk, Ali; Bayram, Yavuz; Ünsaler, Selin; Altuntaş, Ozan; Çetin, Feyza (ENT Updates, 2022)
Background: Clinicians and researchers share their projects in congresses, which are collaborative meetings that enhance the dissemination of information among scientists. Furthermore, critical evaluations of their colleagues help the progress of their research. However, the main focus of any research is publication. In this study, we assess the effect of the European Society of Pediatric Otorhinolaryngology 2018 meeting on the publication rate of abstracts submitted. The aim of this study was to determine whether attending the ESPO 2018 congress had an impact on the publication rate of oral and poster presentations. Methods: All abstracts submitted to the European Society of Pediatric Otorhinolaryngology 2018 Congress catalog were searched in Google Scholar via corresponding title and author to identify the ones that were published. The date of publication, name, and impact factor of the journals of published articles was recorded. Results: A total of 785 abstracts (217 oral, 568 posters) were accepted. Of all abstracts, 21.3% (n = 167) were published. Out of all publications, 32% (n = 53) were oral presentations and 68% (n = 114) were poster presentations. There were 62 different journals with an average weighted 3-year impact factor of 2.06 (±1.09 standard deviation). The 3 most common journals were Int J Pediatr Otorhinolaryngol (n = 49, impact factor: 1.64 ), Laryngoscope (n = 12, impact factor: 2.81 ), and Eur Arch Otorhinolaryngol (n = 10, impact factor: 2.16). Conclusion: Our publication rate of 21.27% is low when compared to oral-only meetings but is similar to others having both oral and poster presentations. We found out that poster presentations reduced the overall publication rate and were published in journals having lower impact factors when compared to oral presentations.